Synthesis and evaluation of the medicinal potential of novel 4-hydroxycoumarin derivatives - Manyeruke, Meloddy Hlatini (Rhodes University, Faculty of Science, Department of Chemistry)
This research has focused on the synthesis and biological evaluation of a broad range of compounds characterised by the presence of the pharmacologically significant 4-hydroxycoumalin scaffold. The compounds were designed to contain additional pharmachophoric centres to enhance bioactivity and generate lead compounds with dualaction potential. The use of 4-hydroxycoumarin as the primary synthon enabled access to various series of 4-hydroxycoumarin conjugates, the reactive 3-position on the 4-hydroxycoumarin moiety being exploited for regioselective construction of the targeted compounds in several steps. Some of the reactants required in the construction of these compounds were specially synthesised and included propargyloxy benzaldehydes, benzyloxy benzaldehydes and 2,3-dihydroxysuccino-dihydride. Overall, eight different families of novel compounds were accessed, comprising conjugates of 4-hydroxycoumarin with bisethylidenesuccinohyrazide, trifluoroacetamide, amino, benzyloxyphenyl-iminoethyl, benzylidenehyrazinyl-thiazoyl, benzylidenehydrazonoethyl, propargyloxybenzylidenehydrazonoethyl and phenylacryloyl moieties using protocols that required minimal work-up and purification. The eighty novel compounds synthesised in the study were fully characterised using HMRS and advanced NMR techniques. Cytotoxicity, HIV-1 IN and PR inhibitory, and antitrypanosomal, antimalarial and anti-Mtb assays were conducted on the synthesised coumarin derivatives. Several compounds exhibited activity against HIV-1 IN, the most potent being a bis-ethylidenesuccinohyrazide with an IC50 value of 3.5 Î¼M. Various compounds exhibited anti-malarial activity (% pLDH viability in the range 62-77%), anti-trypanosomal activity (the most potent with an IC50 = 0.9 Î¼M against T.b. brucei) and a measure of anti-Mtb activity. Apart from two chalconyl derivatives, none of the synthesised compounds exhibited significant cytotoxicity. Conflicting results were obtained from the in silico docking studies; in some cases supporting the observed in vitro assay data while, in others, exhibiting no correlation.
Keywords: 4-hydroxycoumarin; HIV (Viruses); AIDS (Disease); Drug discovery; Coumarins